Pengaruh Volume Penyiraman Air Terhadap Pertumbuhan Benih Tanaman Kakao (Theobroma cacao L.) - Yeni, Indri; Suliansyah, Irfan; Yulistriani, Yulistriani (Jurusan Budidaya Pertanian Fakultas Pertanian Universitas Andalas, 2022)
Nursery is the activities in order to the plants grow uniformly. One of the factors affecting cacao nursery is watering. It aims to fulfill the water needs of plants. Water is important because it is a major component in the cells as compiler of plant tissue. So, the objective of this study was to determine the best volume of water on the growth of cacao seedlings. The research was conducted on September 2019 until January 2020 located in the greenhouse of 3rd Campus Andalas University, Dharmasraya, West Sumatra. The research method was a Completely Randomized Design (CRD) by 4 treatments and 5 replications so obtained 20 experimental units, each of it consisted of 2 cacao seedlings so that 40 plant samples were obtained. Several treatment levels were 150 ml water volume / polybag (V1), 300 ml water volume / polybag (V2), 450 ml water volume / polybag (V3), and 600 ml water volume / polybag (V4). The observation variables were plant height, leaf width, stem diameter, number of leaves, root length and plant dry weight. Regression analysis was performed to know the relationship among observed variables. The results showed that the application of 450 ml water / polybag (V3) generate the best results for plant height, leaf width, stem diameter, number of leaves, plant dry weight, and root length of 1-4 months cacao seedlings. The result of regression analysis showed that there was a close relationship among the plant dry weight of cocoa seedlings with the plant height, stem diameter and number of leaves.